The Leadership Styles of the College Deans - DAGONDON, DR. ROVILYN KATALBAS (The journal of contemporary issues in business and government, 2021)
Leadership styles are essential in the academe world wherein people are more volatile and competitive in the workplace, where leaders should be more flexible to respond to the rapid changes in the working environment, and how to adopt different leadership styles to manage their organizations well. This study focuses on the different leadership styles of college deans in the state universities through the use of a descriptive research method with a total of 260 respondents. Based on the findings of the study, the leadership styles were rated as moderate extent. However, among the six leadership styles of Goleman et.al. (2002), the commanding leadership style got the lowest weighted mean. Hence, there is a need for the improvement on the commanding leadership styles of the college deans in order to have a greater influence to motivate the faculty to perform their work effectively and efficiently.